Peningkatan Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan IPA Menggunakan Model Pembelajaran Artikulasi Di Kelas IX.1 MTs Negeri 1 Palembang - Suhastati Suhastati (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
The problem formulation in this classroom action research is "Can the application of the articulation learning model improve learning outcomes in Natural Sciences subjects for students in class IX.1 MTs Negeri 1 Palembang for the 2020/2021 academic year?" Research results: the application of the articulation learning model can improve student learning outcomes in Natural Sciences subjects in class IX.1 MTs Negeri 1 Palembang for the 2020/2021 academic year. In the pre-cycle (initial condition) the average value of student learning outcomes was 48 with the number of students who completed it being 7 people (25%). In cycle I the average value of student learning outcomes was 70 with the number of students completing it being 15 people (54%). In cycle II the average value of student learning outcomes was 86 with the number of students who completed it being 25 people (89%). So, it can be concluded that this research can be categorized as successful.